1999
DOI: 10.1002/1531-8249(199904)45:4<444::aid-ana5>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Valproate-induced hyperandrogenism during pubertal maturation in girls with epilepsy

Abstract: Valproate is effective for treatment of a variety of seizure types both in adults and in children with epilepsy, but it induces obesity and polycystic ovaries in a considerable proportion of adult women, particularly when the medication is started before the age of 20. In the present study we evaluated reproductive endocrine function in 41 girls, 8 to 18 years old, taking valproate for epilepsy and in 54 healthy control girls. Among the girls taking valproate, 16 were prepubertal, 11 were pubertal, and 14 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1
7

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 27 publications
6
84
1
7
Order By: Relevance
“…The mean serum level of ADION was high in VPA-treated men, and furthermore, more than half of the patients taking VPA had serum levels of testosterone, ADION, or DHEAS above the reference range, which is comparable with the prevalence of hyperandrogenism reported in adult women and young girls taking VPA for epilepsy. 5,6,20 The serum concentration of ADION tended also to be high in a previous study in men taking VPA. 3 In the current study, serum levels of FSH were low in VPA-treated men, which is consistent with a previous observation.…”
Section: Table 4 Body Mass Index (Bmi) Serum Levels Of Insulin Insumentioning
confidence: 61%
See 1 more Smart Citation
“…The mean serum level of ADION was high in VPA-treated men, and furthermore, more than half of the patients taking VPA had serum levels of testosterone, ADION, or DHEAS above the reference range, which is comparable with the prevalence of hyperandrogenism reported in adult women and young girls taking VPA for epilepsy. 5,6,20 The serum concentration of ADION tended also to be high in a previous study in men taking VPA. 3 In the current study, serum levels of FSH were low in VPA-treated men, which is consistent with a previous observation.…”
Section: Table 4 Body Mass Index (Bmi) Serum Levels Of Insulin Insumentioning
confidence: 61%
“…In our previous study, hyperandrogenemia was common among young girls (aged 8 to 18 years) taking VPA for epilepsy, but the girls with hyperandrogenemia were not hyperinsulinemic, though their BMI tended to be higher than that of the control girls. 20,23 Therefore, in men and young girls, VPA-related hyperandrogenism is not associated with hyperinsulinemia, nor is it induced by increased LH stimulation. Accordingly, VPA-related hyperandrogenism does not seem to be mediated through changes in the serum concentrations of other hormones.…”
Section: Table 4 Body Mass Index (Bmi) Serum Levels Of Insulin Insumentioning
confidence: 99%
“…It is not known whether such effects are due to the epilepsy itself or the antiepileptic drugs [26]. CBZ treatment has been reported to cause hyposexuality, impotence and menstrual disorders in adults by influencing the levels of sex steroids and SHBG.…”
Section: Discussionmentioning
confidence: 99%
“…The first report suggesting a high incidence of menstrual disorders linked to obesity, hyperandrogenism, and polycystic ovaries in women taking VPA for epilepsy was published in 1993 (Isojarvi). Changes in serum androgen levels have been detected before and during pubertal development in young girls taking VPA for epilepsy (Vainionpää, 1999). Studies by Murialdo et al (1997) have also reported a high prevalence of menstrual disorders and hyperandrogenic anovulation in VPA treated women with epilepsy.…”
Section: Epilepsy and Polycystic Ovary Syndromementioning
confidence: 99%